Innovation the Success of Micro, Small, and Medium Enterprises in Medan City - Bancin, Aswin; Julita, Julita (AIBPM Publisher, 2023)
This study discusses the success of Micro, Small, and Medium Enterprises in Medan City. The purpose of this research focuses on the process of innovation that mediates the success of SMEs. The success of SMEs is tested by involving Entrepreneurial Competency Factors and Environment-mediated Business Innovation. This study took the population of MSME actors in Medan City with a sample of 100 respondents. The data obtained were analyzed by means of quantitative data analysis using the Structural Equation Modeling (SEM) method. The research results showed that Innovation mediates the effect of Entrepreneurial Competence on the success of MSMEs in Medan City, and Innovation mediates the Effects of the Business Environment on the success of MSMEs.